The Role of Lipotoxicity in Smoke Cardiomyopathy - Santos, Priscila P. [UNESP]; Oliveira, Fernando [UNESP]; Ferreira, Vanessa C. M. P. [UNESP]; Polegato, Bertha Furlan [UNESP]; Roscani, Meliza Goi [UNESP]; Fernandes, Ana Angelica [UNESP]; Modesto, Pamela [UNESP]; Rafacho, Bruna P. M. [UNESP]; Zanati, Silmeia G. [UNESP]; Di Lorenzo, Annarita; Matsubara, Luiz Shiguero [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; et al. (Public Library Science, 2014)
Background/Aims: Experimental and clinical studies have shown the direct toxic effects of cigarette smoke (CS) on the myocardium, independent of vascular effects. However, the underlying mechanisms are not well known.Methods: Wistar rats were allocated to control (C) and cigarette smoke (CS) groups. CS rats were exposed to cigarette smoke for 2 months.Results: After that morphometric, functional and biochemical parameters were measured. The echocardiographic study showed enlargement of the left atria, increase in the left ventricular systolic volume and reduced systolic function. Within the cardiac metabolism, exposure to CS decreased beta hydroxy acyl coenzyme A dehydrogenases and citrate synthases and increased lactate dehydrogenases. Peroxisome proliferator-activated receptor alpha (PPAR alpha) and peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC-1 alpha) were expressed similarly in both groups. CS increased serum lipids and myocardial triacylglycerols (TGs). These data suggest that impairment in fatty acid oxidation and the accumulation of cardiac lipids characterize lipotoxicity. CS group exhibited increased oxidative stress and decreased antioxidant defense. Finally, the myocyte cross-sectional area and active Caspase 3 were increased in the CS group.Conclusion: The cardiac remodeling that was observed in the CS exposure model may be explained by abnormalities in energy metabolism, including lipotoxicity and oxidative stress.